2016
DOI: 10.1007/s11095-016-2018-x
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Imaging Approaches to Assess Drug Release from Multicomponent Solid Dispersions

Abstract: PurposeImaging methods were used as tools to provide an understanding of phenomena that occur during dissolution experiments, and ultimately to select the best ratio of two polymers in a matrix in terms of enhancement of the dissolution rate and prevention of crystallization during dissolution.MethodsMagnetic resonance imaging, ATR-FTIR spectroscopic imaging and Raman mapping have been used to study the release mechanism of a poorly water soluble drug, aprepitant, from multicomponent amorphous solid dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Ninety-two of the 101 studies reported solubility and dissolution studies ( 71 74 , 77 79 , 81 92 , 95 , 97 107 , 109 111 , 113 119 , 121 , 123 , 124 , 126 133 , 135 139 , 141 154 , 156 , 157 , 160 , 161 , 166 , 168 176 ). The USP in vitro dissolution type II apparatus was the most commonly used instrument (67%), followed by the USP type I apparatus (6%), while the remaining 27% used various other apparatuses, including modified versions of the USP type I only ( 148 ) or paired with confocal Raman microscopy ( 98 ), USP types I and II apparatus ( 72 ), USP type IV ( 152 ), closed loop of USP types II and IV ( 152 ), a perspex flow cell ( 73 , 142 ), a rotary mixer ( 131 ), a Chinese pharmacopoeia type III apparatus ( 118 ), an in-house miniaturized USP type II apparatus ( 175 ), Sirius T3 apparatus ( 146 ), μFLUX dissolution-permeation apparatus ( 141 ), Raman UV-Vis flow cell system ( 99 ), a centrifuge ( 88 ), high throughput screening using a 96-well plate ( 82 , 115 , 157 ), Wood’s apparatus ( 99 , 137 ), an orbital shaking incubator ( 156 ), and another shake-flask method ( 171 ) (Fig. 6 ).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety-two of the 101 studies reported solubility and dissolution studies ( 71 74 , 77 79 , 81 92 , 95 , 97 107 , 109 111 , 113 119 , 121 , 123 , 124 , 126 133 , 135 139 , 141 154 , 156 , 157 , 160 , 161 , 166 , 168 176 ). The USP in vitro dissolution type II apparatus was the most commonly used instrument (67%), followed by the USP type I apparatus (6%), while the remaining 27% used various other apparatuses, including modified versions of the USP type I only ( 148 ) or paired with confocal Raman microscopy ( 98 ), USP types I and II apparatus ( 72 ), USP type IV ( 152 ), closed loop of USP types II and IV ( 152 ), a perspex flow cell ( 73 , 142 ), a rotary mixer ( 131 ), a Chinese pharmacopoeia type III apparatus ( 118 ), an in-house miniaturized USP type II apparatus ( 175 ), Sirius T3 apparatus ( 146 ), μFLUX dissolution-permeation apparatus ( 141 ), Raman UV-Vis flow cell system ( 99 ), a centrifuge ( 88 ), high throughput screening using a 96-well plate ( 82 , 115 , 157 ), Wood’s apparatus ( 99 , 137 ), an orbital shaking incubator ( 156 ), and another shake-flask method ( 171 ) (Fig. 6 ).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…6 ). In several of these studies, dissolution apparatuses were either modified, optimized or paired with other instruments and methods to enable the investigation, monitoring, and understanding of other processes that take place concurrently with dissolution such as permeation ( 141 ), release mechanisms ( 73 , 98 , 99 , 101 , 106 , 142 ) and wetting kinetics ( 71 ). The experimental conditions during in vitro dissolution testing (e.g.…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…29 In the present study, these different mechanisms act together to improve ITZ dissolution and may be the reason why the combination of the polymers has led to a better drug dissolution. 30 In Vitro Taste-Masking Evaluation E-tongue sensors imitate taste bud on human tongue by initiating changes in electric potentials that can be compared to physiological action. 31 This in vitro assay presents a high correlation with human sensory test and is until 100 times more sensitive for bitter taste than human panel.…”
Section: Dissolution Testsmentioning
confidence: 99%
“…In this context, the development of novel formulations containing aprepitant that may enhance its solubility and bioavailability is considered of great importance for the reduction of the required dose [8,12,13]. A broad range of methods have been proposed for co-formulating aprepitant with different carriers for oral delivery, including micro-emulsions [14,15], self-emulsified drug delivery systems (SEDDS) [16], solid dispersions [17][18][19][20][21], hot-melt extrusion [18], liquisolid formulations [22], and inclusion complexes (cyclodextrins) [13,23].…”
Section: Introductionmentioning
confidence: 99%
“…A broad range of methods have been proposed for co-formulating aprepitant with different carriers for oral delivery, including micro-emulsions [ 14 , 15 ], self-emulsified drug delivery systems (SEDDS) [ 16 ], solid dispersions [ 17 , 18 , 19 , 20 , 21 ], hot-melt extrusion [ 18 ], liquisolid formulations [ 22 ], and inclusion complexes (cyclodextrins) [ 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%